α-catenin interaction with YAP/FoxM1/TEAD-induced CEP55 supports liver cancer cell migration - Tang, Yingyue; Thiess, Lena; Weiler, Sofia Maria Elisabeth; Tóth, Marcell; Rose, Fabian; Merker, Sabine; Ruppert, Thomas; Schirmacher, Peter; Breuhahn, Kai (Cell communication and signaling, 2023)
Adherens junctions (AJs) facilitate cell-cell contact and contribute to cellular communication as well as signaling under physiological and pathological conditions. Aberrant expression of AJ proteins is frequently observed in human cancers; however, how these factors contribute to tumorigenesis is poorly understood. In addition, for some factors such as α‐catenin contradicting data has been described. In this study we aim to decipher how the AJ constituent α‐catenin contributes to liver cancer formation.